Polyurethane foam and preparation method thereof

By optimizing the distribution ratio and preparation method of polyurethane foam, the application restriction of polyurethane foam in high viscosity and high thixotropy requirements is solved, and high viscosity, high thixotropy and excellent waterproof sealing performance is achieved. Its application field and improves flame retardancy and mechanical properties.

CN118725808BActive Publication Date: 2025-01-03KEJIAN POLYMER MATERIALS (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411225705.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-03
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Existing polyurethane foam glue is limited in high viscosity and high thixotropy demand scenarios, lacks water absorption and waterproof sealing, and has problems such as large odor, poor flame retardancy and poor mechanical properties, which cannot meet modular industrial products. performance requirements.

Method used

Polyurethane foam glue with high viscosity and high thixotropy properties is formed by using components such as polyol compositions, chain extenders, flame retardants, functional particles, thixotropy agents and functional polymers through specific proportions and preparation methods. , ensure high environmentally friendly flame retardancy without halogen and phosphorus, and improve waterproof sealing and mechanical properties through the composite modified structure of functional particles.

Benefits of technology

It realizes the high viscosity and high thixotropy properties of polyurethane foam, improves water absorption and waterproof sealing, expands the application field and environment, avoids the problems of degradation of mechanical properties and increasing odor, and meets the flat and inclined surface glueing. industrial demand and improve flame retardant and waterproofing properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118725808B_ABST
    Figure CN118725808B_ABST
Patent Text Reader

Abstract

The present application relates to the field of foaming glue, and in particular to a polyurethane foaming glue and a preparation method thereof. The polyurethane foaming glue comprises components A and B; the raw materials of component A are 65-85 parts of polyol composition, 2-5 parts of chain extender, 10-20 parts of flame retardant, 10-15 parts of functional particles, 2-5 parts of thixotropic agent, 0.3-1 parts of catalyst, 1.5-3 parts of foam stabilizer, 1-2 parts of deionized water, 0.4-0.8 parts of antioxidant, and 1.5-2.5 parts of auxiliary agent in parts by mass; the raw materials of component B are 45-55 parts of polyisocyanate and 45-55 parts of functional polymer in parts by mass. The polyurethane foaming glue prepared in the present application is halogen-free and phosphorus-free, environmentally friendly and flame-retardant. Through the design of high viscosity and high thixotropy, it effectively meets the industrial needs of gluing on planes and inclined surfaces, greatly improves its water absorption rate, improves waterproof sealing and mechanical property retention rate, and has very excellent application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of foaming glue, and in particular to a polyurethane foaming glue and a preparation method thereof. Background Art

[0002] Polyurethane foam is a special product that is commonly used in the fields of automobiles, building decoration, electrical appliances, etc. It is mainly used for filling, bonding, sealing, and sound insulation and heat insulation. At present, there are many types of polyurethane foam products on the market, and with the improvement of environmental protection in recent years, the environmental protection of most polyurethane foams has been greatly improved.

[0003] At the same time, most of the existing polyurethane foams are low-viscosity self-leveling products, which cannot be used directly when facing high viscosity and high thixotropy requirements. This greatly affects the expansion of the application fields and application environments of polyurethane foams. In addition, the water absorption resistance and waterproof sealing properties of existing polyurethane foams have become poor due to changes in raw material solutions, and some existing polyurethane foam products still have the disadvantages of strong odor, poor flame retardancy, poor mechanical properties and high density, and thus cannot adapt to the performance requirements of existing modular industrial products for polyurethane foams.

[0004] Therefore, in order to solve the above problems, the present application provides a polyurethane foam and a preparation method thereof. The polyurethane foam prepared in the present application can effectively meet the industrial needs of gluing on flat and inclined surfaces and greatly improve its water absorption and waterproof sealing properties, while ensuring halogen-free and phosphorus-free high environmental protection and flame retardancy, and has excellent high viscosity and high thixotropic properties of the foam; on the other hand, the polyurethane foam prepared in the present application can also effectively avoid the problems of obvious decrease in mechanical properties and increase in odor caused by the above-mentioned performance modification of the polyurethane foam, greatly expanding the application field and application environment of the polyurethane foam, and has excellent application prospects. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides a polyurethane foam, including component A and component B;

[0006] The raw materials of component A are calculated by weight: 65-85 parts of polyol composition, 2-5 parts of chain extender, 10-20 parts of flame retardant, 10-15 parts of functional particles, 2-5 parts of thixotropic agent, 0.3-1 parts of catalyst, 1.5-3 parts of foam stabilizer, 1-2 parts of deionized water, 0.4-0.8 parts of antioxidant, and 1.5-2.5 parts of auxiliary agent;

[0007] The raw materials of the B component are, by weight, 45-55 parts of polyisocyanate and 45-55 parts of functional polymer.

[0008] As a preferred solution, the mass ratio of component A to component B is (95-100):(15-22).

[0009] As a preferred solution, the mass ratio of component A to component B is 100:(17-20).

[0010] As a preferred solution, the mass ratio of the polyol composition, the functional particles and the additives is (70-80): (12-15): (1.8-2.2).

[0011] As a preferred embodiment, the mass ratio of the polyol composition, the functional particles and the auxiliary agent is (73-76): (13-14): (1.9-2).

[0012] As a preferred solution, the polyol composition is a composition of polyether polyol and polyurea polyol.

[0013] As a preferred solution, the mass ratio of the polyether polyol to the polyurea polyol is (40-50):(25-35).

[0014] As a preferred solution, the mass ratio of the polyether polyol to the polyurea polyol is 40:35.

[0015] As a preferred solution, the polyether polyol is propylene oxide-ethylene oxide copolyether triol.

[0016] As a preferred solution, the primary hydroxyl content of the propylene oxide-ethylene oxide copolyether triol is 70-90%.

[0017] As a preferred solution, the weight average molecular weight of the propylene oxide-ethylene oxide copolyether triol is 4500~5500Da.

[0018] As a preferred solution, the hydroxyl value of the propylene oxide-ethylene oxide copolyether triol is 34-38 mgKOH / g.

[0019] As a preferred solution, the viscosity of the propylene oxide-ethylene oxide copolyether triol is 800-1000 mPa·s at 25°C.

[0020] As a preferred solution, the polyurea polyol includes a benzene ring structure.

[0021] As a preferred solution, the polyurea content of the polyurea polyol is 15-25%.

[0022] As a preferred solution, the hydroxyl value of the polyurea polyol is 24-26 mgKOH / g.

[0023] As a preferred solution, the viscosity of the polyurea polyol is 1800-2400 mPa·s at 25°C.

[0024] As a preferred solution, the chain extender is at least one of ethylene glycol, triethanolamine, diethyltoluenediamine, and polytetramethylene ether glycol bis(p-aminobenzoate).

[0025] As a preferred solution, the chain extender is polytetramethylene ether glycol bis-p-aminobenzoate.

[0026] As a preferred solution, the flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, zinc borate, antimony oxide, expanded graphite, and aluminum oxide.

[0027] As a preferred solution, the flame retardant is a combination of aluminum hydroxide and zinc borate.

[0028] As a preferred solution, the mass ratio of aluminum hydroxide to zinc borate is (4-6): (1-1.5).

[0029] As a preferred solution, the mass ratio of the aluminum hydroxide to the zinc borate is 5:1.

[0030] As a preferred solution, the average particle size of the flame retardant is 1-3 μm.

[0031] As a preferred solution, the average particle size of the flame retardant is 1.5-2 μm.

[0032] As a preferred scheme, the preparation method of the functional particles includes the following steps: S1: adding zinc oxide to a DMF solution, adding succinic anhydride and vinyl trimethoxysilane, heating to 70-75°C and keeping warm for 2-4 hours, centrifugally filtering after completion, washing with deionized water and drying to obtain pretreated zinc oxide; S2: mixing the pretreated zinc oxide and zinc nitrate hexahydrate and adding them to DMF, heating to 60-65°C and keeping warm for 30-40 minutes, dropwise adding a DMF solution of 2,5-dihydroxyterephthalic acid, heating to 68-70°C, and stirring at 60-80 rpm for 2-2.5 hours; S3: adding amylose, cooling to 45-50°C, rapidly stirring at 120-160 rpm for reaction for 0.5-1 hour, centrifugally filtering the product after completion, adding it to deionized water, and ultrasonically vibrating at 300-400W for 2-3 hours until there is no block precipitation in the solution, and centrifugally filtering the product after completion and freeze-drying, and the product is obtained after completion.

[0033] As a preferred solution, the mass ratio of zinc oxide, succinic anhydride and vinyltrimethoxysilane is (3-3.5): (1.5-2): (0.2-0.3).

[0034] As a preferred solution, the mass ratio of the pretreated zinc oxide, zinc nitrate hexahydrate, 2,5-dihydroxyterephthalic acid and amylose is (1-1.5): (1.2-2): (2.5-3.5): (1.2-1.6).

[0035] As a preferred solution, the mass ratio of the pretreated zinc oxide, zinc nitrate hexahydrate, 2,5-dihydroxyterephthalic acid and amylose is (1.1-1.3): (1.4-1.8): (2.8-3.2): (1.4-1.5).

[0036] As a preferred solution, the average particle size of the zinc oxide is 10-20 nm.

[0037] The functional particles added in this application can greatly improve the viscosity, thixotropy, waterproof sealing and mechanical properties of polyurethane foam. The functional particles after composite modification can form a combined structure with amylose as the main carrier, nano zinc oxide and framework particles. The existence of this structure can participate in the formation of carbamate bonds in polyurethane foam through the hydroxyl groups in amylose, provide good active sites in the network construction of polyurethane, and greatly enhance the dispersion uniformity of functional particles and other particles in the polyurethane foam system and the subsequent dispersion fixation strength during the application process, thereby avoiding the migration and aggregation of particles inside the system; on the other hand, the composite structure of zinc oxide and framework particles formed can effectively remove the moisture system inside the polyurethane foam through its guidance and absorption of internal trace moisture, greatly increase the free resistance and penetration resistance of moisture in the system, and can form a good barrier layer, thereby greatly weakening the aggregation of water molecules, reducing the formation speed of hydration layer or agglomerated water, and thus obtaining excellent thixotropy, waterproof and other properties.

[0038] As a preferred solution, the thixotropic agent is a composition of bentonite and modified hydrogenated castor oil.

[0039] As a preferred solution, the modified hydrogenated castor oil is polyamide-modified hydrogenated castor oil.

[0040] As a preferred solution, the mass ratio of the bentonite to the modified hydrogenated castor oil is (1.2-1.6): (2.5-3.5).

[0041] As a preferred solution, the mass ratio of the bentonite to the modified hydrogenated castor oil is (1.4-1.5): (2.8-3.2).

[0042] As a preferred solution, the catalyst is a mixed solution of triethylenediamine and modified triethylenediamine.

[0043] As a preferred solution, the foam stabilizer is a hydrosilylation polymer of improved polyether and polysiloxane.

[0044] As a preferred solution, the improved polyether and polysiloxane hydrosilylation polymer is a composition of a polymer having a viscosity of 750-1250 mPa·s at 25°C and a polymer having a viscosity of 2000-2400 mPa·s at 25°C.

[0045] As a preferred solution, the mass ratio of the polymer with a viscosity of 750-1250 mPa·s at 25°C to the polymer with a viscosity of 2000-2400 mPa·s at 25°C is (1.3-1.6): (0.4-0.6).

[0046] As a preferred solution, the auxiliary agent is at least one of polyisobutylene, terminal hydroxyl-modified polybutadiene, hydrogenated rosin methyl ester, and liquid petroleum resin.

[0047] As a preferred solution, the auxiliary agent is terminal hydroxyl-modified polybutadiene.

[0048] As a preferred solution, the hydroxyl value of the terminal hydroxyl-modified polybutadiene is 44-51 mgKOH / g; the viscosity of the terminal hydroxyl-modified polybutadiene is 4000-5000 mPa·s at 25°C.

[0049] As a preferred solution, the polyisocyanate is at least one of polymethylene polyphenyl isocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and cyclohexyl diisocyanate.

[0050] As a preferred solution, the polyisocyanate is polymethylene polyphenyl isocyanate.

[0051] As a preferred solution, the functional polymer is a polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate.

[0052] As a preferred solution, the preparation method of the functional polymer comprises the following steps: vacuum dehydrating trimer 1,2-propylene glycol at 120-130°C for 1.5-2h, then adding diphenylmethane diisocyanate, stirring and heating to 80-90°C, keeping the temperature for reaction for 2h, cooling to 60-65°C and discharging, and after completion, a polymer of trimer 1,2-propylene glycol and diphenylmethane diisocyanate is obtained.

[0053] As a preferred solution, the mass ratio of trimer 1,2-propylene glycol to diphenylmethane diisocyanate is (1-1.5):(4-4.5).

[0054] As a preferred solution, the NCO content index of the functional polymer is 20-24%.

[0055] As a preferred solution, the viscosity of the functional polymer is 1000-1500 mPa·s at 25°C.

[0056] The polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate added in the present application can greatly improve the mechanical properties, thixotropy and water resistance of polyurethane foam, and effectively ensure flame retardancy. The polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate added in the present application, in addition to being able to participate in the construction of the main chain structural unit in the formation of polyurethane foam, can introduce branch points in the polyurethane network structure through the polyhydroxy contained therein, thereby greatly strengthening the intermolecular attraction activity of the long molecular chain with other molecular chains and raw materials inside, and greatly improving the strength and density of the constructed cross-linked network; at the same time, relying on the high reactivity of diphenylmethane diisocyanate in the mixed components A and B, greatly increasing the generation efficiency of the carbamate chain, under the influence of moisture, quickly constructing a stable foaming structure, and through the good connection force with other particles such as the added functional particles, the dispersed position of the solidified particles in the system, reducing the internal migration of its particles when in use, and can also improve the degree of internal stress tolerance under the action of external forces, so that the foam obtains excellent mechanical properties, water resistance and flame retardancy.

[0057] As a preferred solution, the NCO content index of the B component is 26-27%, and the viscosity is 400-600 mPa·s at 25°C.

[0058] The second aspect of the present application provides a method for preparing the above-mentioned polyurethane foam, which specifically includes the following steps: S1: adding a polyol composition, a chain extender, a flame retardant, functional particles and a thixotropic agent into a reactor and mixing and stirring until there are no obvious undispersed particles, then heating to 70-90°C, stirring and reacting at a speed of 200-300rpm for 50-70min, and then cooling to 30-35°C at 1-1.5°C / min to obtain a premixed base material; S2: adding deionized water to the premixed base material to control the moisture content at 1.2-2wt%, then adding a foam stabilizer and a catalyst, stirring and dispersing for 30-50min, and then blowing at a speed of 100-150rpm for mixing for 20-30min to obtain component A; S3: adding a polyisocyanate and a functional polymer into a vacuum reactor, heating to 60-65°C and stirring at a speed of 40-60rpm for 30-40min, and nitrogen breaking through the air to produce glue to obtain component B; S4: when using, component A and component B are mixed and glued according to a proportion, and the result is obtained after completion.

[0059] The beneficial effects of this application are:

[0060] 1. A polyurethane foam adhesive provided in the present application can effectively meet the industrial needs of gluing flat and inclined surfaces and greatly improve its water absorption and waterproof sealing properties while ensuring halogen-free and phosphorus-free high environmental protection and flame retardancy, and has excellent high viscosity and high thixotropic properties of the foam adhesive; on the other hand, the polyurethane foam adhesive prepared in the present application can also effectively avoid the problems of obvious decrease in mechanical properties and increase in odor caused by the above-mentioned performance modification of the polyurethane foam adhesive, greatly expanding the application field and application environment of the polyurethane foam adhesive, and has excellent application prospects.

[0061] 2. The polyurethane foam provided in the present application has good flame retardancy and environmental protection properties, strong waterproof sealing properties, and can be used for sealing automotive modular door panels and electrical cabinets. Through mechanized gluing, stable foaming of flat, inclined and other grooveless panels can be achieved without glue flow or overflow, while meeting the requirements of long gluing time for large pieces and fast curing requirements for fast-paced production.

[0062] 3. The polyurethane foam provided in the present application can greatly improve the viscosity, thixotropy, waterproof sealing and mechanical properties of the polyurethane foam by adding functional particles; the functional particles after composite modification can form a combined structure with amylose as the main carrier, nano-zinc oxide and framework particles as the coordination, and the existence of this structure can participate in the formation of carbamate bonds in the polyurethane foam through the hydroxyl groups in the amylose, provide good active sites in the network construction of the polyurethane, and thus greatly enhance the dispersion uniformity of the functional particles and other particles in the polyurethane foam system and the subsequent dispersion fixation strength during the application process, thereby avoiding the migration and aggregation of particles inside the system, and can also effectively remove the moisture system inside the polyurethane foam by guiding and absorbing the internal trace moisture through the composite structure, thereby greatly increasing the free resistance and penetration resistance of moisture in the system.

[0063] 4. A polyurethane foam provided in the present application, wherein the polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate added therein can greatly improve the mechanical properties, thixotropy and waterproof properties of the polyurethane foam, and can participate in the construction of the main chain structural unit in the formation of the polyurethane foam, and can introduce branching points in the polyurethane network structure through the polyhydroxy groups it contains, thereby greatly enhancing the intermolecular attraction activity of the long molecular chain with other molecular chains and raw materials inside, and greatly improving the strength and density of the constructed cross-linked network; at the same time, relying on the high reactivity of diphenylmethane diisocyanate in the mixed components A and B, the generation efficiency of the carbamate chain is greatly increased, and under the influence of moisture, a stable foaming structure is quickly constructed, and through the good connection force with other particles such as the added functional particles, the dispersed position of the solidified particles in the system is reduced, and the internal migration of the particles is reduced during use, and the internal stress tolerance under the action of external forces can also be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is a schematic diagram of the U-shaped waterproof test results of Example 1 of the present application; Figure a is the initial test diagram, the test depth is 100mm, and Figure b is the test result diagram after 60 minutes. DETAILED DESCRIPTION

[0065] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0066] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0067] Example 1

[0068] Embodiment 1 A first aspect provides a polyurethane foam adhesive, comprising component A and component B;

[0069] The raw materials of component A are calculated by weight: 75 parts of polyol composition, 2 parts of chain extender, 12 parts of flame retardant, 13.5 parts of functional particles, 4.5 parts of thixotropic agent, 0.6 parts of catalyst, 2 parts of foam stabilizer, 1.4 parts of deionized water, 0.5 parts of antioxidant, and 2 parts of additives;

[0070] The raw materials of component B are calculated by weight: 50 parts of polyisocyanate and 50 parts of functional polymer.

[0071] The mass ratio of component A to component B is 100:18.2.

[0072] The polyol composition is a composition of polyether polyol and polyurea polyol, and the mass ratio of the two is 40:35.

[0073] The polyether polyol is propylene oxide-ethylene oxide copolyether triol, purchased from Changhua Chemical Technology Co., Ltd., model CHE-330N product, with a primary hydroxyl content of 82%, a weight average molecular weight of 5000 Da, a hydroxyl value of 35.5 mg KOH / g, and a viscosity of 824 mPa·s at 25°C.

[0074] The polyurea polyol includes a benzene ring structure and is purchased from Jiangyin Youbang Chemical Co., Ltd., a YB-3083 product sold by the company. The polyurea content is 18%, the hydroxyl value is 25.4 mgKOH / g, the viscosity is 2000 mPa·s, and the temperature is 25°C.

[0075] The chain extender is polytetramethylene ether glycol bis-p-aminobenzoate, which is purchased from Suzhou Xiangyuan New Materials Co., Ltd. and is a P-1000 product.

[0076] The flame retardant is a composition of aluminum hydroxide and zinc borate, the mass ratio of the two is 5:1, and the average particle size of the composition is 1.8 μm.

[0077] The preparation method of functional particles comprises the following steps, calculated by mass: S1: adding 3.2 parts of zinc oxide to 60 parts of DMF solution, adding 1.8 parts of succinic anhydride and 0.25 parts of vinyl trimethoxy silane, heating to 72°C and keeping warm for 3.2 hours, centrifugally filtering after completion, washing with deionized water and drying to obtain pretreated zinc oxide; S2: adding 1.2 parts of pretreated zinc oxide and 1.5 parts of zinc nitrate hexahydrate to 80 parts of DMF, heating to 62°C and keeping warm for 40 minutes, dropwise adding 3.1 parts of DMF solution of 2,5-dihydroxyterephthalic acid (a total of 25 parts), heating to 70°C, stirring at 80 rpm for 2 hours; S3: adding 1.4 parts of amylose, cooling to 45°C, rapidly stirring at 150 rpm for reaction for 0.5 hours, centrifugally filtering the product after completion, adding it to deionized water, ultrasonically vibrating at 400W for 2.5 hours until there is no block precipitation in the solution, centrifugally filtering the product after completion and freeze-drying, and obtaining the particle after completion.

[0078] The average particle size of zinc oxide is 16 nm.

[0079] The amylose was purchased from the amylose product sold by Wuhan Huaxiang Kejie Biotechnology Co., Ltd., with an amylose content of 71.2%.

[0080] The thixotropic agent is a composition of bentonite and modified hydrogenated castor oil, with a mass ratio of 1.5:3. The modified hydrogenated castor oil is polyamide-modified hydrogenated castor oil, purchased from Hemmings Deqian under the model THIXATROL-ST. The bentonite is purchased from the model GARAMITE 1958 sold by BYK Chemical.

[0081] The catalyst is a mixed solution of triethylenediamine and modified triethylenediamine. The triethylenediamine is purchased from NIAX Catalyst A-33 sold by Momentive, and the modified triethylenediamine is purchased from DABCO 1027 sold by Air Products and Chemicals. The mass ratio of NIAX Catalyst A-33 to DABCO1027 is 0.4:0.2.

[0082] The foam stabilizer is a modified silane addition polymer of polyether and polysiloxane, and the modified silane addition polymer of polyether and polysiloxane is a composition of a polymer with a viscosity of 900 mPa·s at 25°C (purchased from the Y-10366 model product sold by Momentive Corporation) and a polymer with a viscosity of 2000 mPa·s at 25°C (purchased from the LK-3360 model product sold by Shanghai Yexing Industrial Co., Ltd.), and the mass ratio of the two is 1.5:0.5.

[0083] The antioxidant was purchased from Clariant under the model number AddWorks IBC 760.

[0084] The auxiliary agent is terminal hydroxyl-modified polybutadiene, which is purchased from Evonik and has a hydroxyl value of 45.6 mgKOH / g. The viscosity of the terminal hydroxyl-modified polybutadiene is 4400 mPa·s at 25°C.

[0085] The polyisocyanate is polymethylene polyphenyl isocyanate.

[0086] The functional polymer is a polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate. The preparation method comprises the following steps, calculated by mass: 20 parts of trimerized 1,2-propylene glycol are vacuum dehydrated at 120°C for 1.5 hours, then 80 parts of diphenylmethane diisocyanate are added, stirred and heated to 80°C, kept warm for reaction for 2 hours, cooled to 60°C and discharged, and after completion, a polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate is obtained.

[0087] The NCO content index of the functional polymer is 22.4%, and the viscosity is 1200 mPa·s at 25°C.

[0088] The NCO content index of component B is 26.8%, and the viscosity is 550 mPa·s at 25°C.

[0089] The second aspect of the present embodiment provides a method for preparing the above-mentioned polyurethane foam, which specifically includes the following steps: S1: adding a polyol composition, a chain extender, a flame retardant, functional particles and a thixotropic agent into a reactor and mixing and stirring until there are no obvious undispersed particles, then heating to 80°C, stirring at 280rpm for 60min, and then cooling to 35°C at 1°C / min to obtain a premixed base material; S2: adding deionized water to the premixed base material to control the moisture content at 1.2wt%, then adding a foam stabilizer and a catalyst, stirring and dispersing for 40min, and then blowing at 120rpm for 30min to obtain component A; S3: adding polyisocyanate and functional polymer into a vacuum reactor, heating to 62°C and stirring at 55rpm for 40min, nitrogen breaking through the air to produce glue, and obtaining component B; S4: when using, mix component A and component B according to a proportion and glue them, and the result is obtained after completion.

[0090] Example 2

[0091] The specific implementation of this embodiment is basically the same as that of Embodiment 1, except that the polyol composition is a composition of polyether polyol and polyurea polyol, and the mass ratio of the two is 45:30.

[0092] The catalyst is a mixed solution of triethylenediamine and modified triethylenediamine. The triethylenediamine is purchased from NIAX Catalyst A-33 sold by Momentive, and the modified triethylenediamine is purchased from DABCO 1027 sold by Air Products and Chemicals. The mass ratio of NIAX Catalyst A-33 to DABCO1027 is 0.45:0.1.

[0093] Example 3

[0094] The specific implementation of this embodiment is basically the same as that of Embodiment 1, except that the polyol composition is a composition of polyether polyol and polyurea polyol, and the mass ratio of the two is 50:25.

[0095] The catalyst is a mixed solution of triethylenediamine and modified triethylenediamine. The triethylenediamine is purchased from NIAX Catalyst A-33 sold by Momentive, and the modified triethylenediamine is purchased from DABCO 1027 sold by Air Products and Chemicals. The mass ratio of NIAX Catalyst A-33 to DABCO 1027 is 0.5:0.1.

[0096] Comparative Example 1

[0097] The specific implementation of this comparative example is basically the same as that of Example 1, except that the polyol composition is a composition of polyether polyol and polyurea polyol, the mass ratio of the two is 40:35, but the polyurea polyol is a 10LD28ZJ model product sold by Shandong Bluestar Dongda Co., Ltd., does not contain a benzene ring structure, has a hydroxyl value of 30 mgKOH / g, a viscosity of 800 mPa·s, and a temperature of 25°C.

[0098] Comparative Example 2

[0099] The specific implementation of this comparative example is basically the same as that of Example 1, except that the thixotropic agent is a composition of fumed silica and modified urea oligomer, and the mass ratio of the two is 4:0.5. The fumed silica is purchased from Aerosil 200 sold by Degussa; the modified urea oligomer is purchased from RHEOBYK-410 sold by BYK Chemical.

[0100] Comparative Example 3

[0101] The specific implementation of this comparative example is basically the same as that of Example 1, except that the thixotropic agent is a composition of bentonite and modified hydrogenated castor oil, and the mass ratio of the two is 4:1.

[0102] Comparative Example 4

[0103] The specific implementation of this comparative example is basically the same as that of Example 1, except that the catalyst does not include modified triethylenediamine, and the catalyst is NIAX Catalyst A-33 and NIAX Catalyst C-225 purchased from Momentive, with a mass ratio of 0.3:0.2.

[0104] Comparative Example 5

[0105] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of component A, calculated by mass, are: 87 parts of polyol composition, 2 parts of chain extender, 12 parts of flame retardant, 13.5 parts of functional particles, 4.5 parts of thixotropic agent, 0.6 parts of catalyst, 2 parts of foam stabilizer, 1.4 parts of deionized water, 0.5 parts of antioxidant, and 0.5 parts of auxiliary agent.

[0106] Comparative Example 6

[0107] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional particles comprises the following steps, calculated by mass: S1: adding 5.5 parts of zinc oxide to 80 parts of DMF solution, adding 1.1 parts of succinic anhydride and 0.1 parts of vinyltrimethoxysilane, heating to 72°C and keeping warm for 3.2 hours, centrifuging and filtering after completion, washing with deionized water and drying to obtain pretreated zinc oxide; S2: mixing 1.2 parts of pretreated zinc oxide and 1.5 parts of zinc nitrate hexahydrate and adding to 80 parts of DMF solution; In MF, heat to 62°C and keep warm for 40 minutes, add dropwise 3.1 parts of 2,5-dihydroxyterephthalic acid DMF solution (25 parts in total), heat to 70°C, and stir at 80rpm for 2h; S3: add 1.4 parts of amylose, cool to 45°C, and react with rapid stirring at 150rpm for 0.5h. After completion, centrifuge and filter the product, add it to deionized water, and ultrasonically vibrate at 400W for 2.5h until there is no lumpy precipitate in the solution. After completion, the product is centrifuged and filtered and freeze-dried. After completion, it is obtained.

[0108] Comparative Example 7

[0109] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional particles comprises the following steps, calculated by mass: S1: adding 3.2 parts of zinc oxide to 60 parts of DMF solution, adding 1.8 parts of succinic anhydride and 0.25 parts of vinyltrimethoxysilane, heating to 72°C and keeping warm for 3.2 hours, centrifuging and filtering after completion, washing with deionized water and drying to obtain pretreated zinc oxide; S2: mixing 2.8 parts of pretreated zinc oxide and 0.9 parts of zinc nitrate hexahydrate and adding to 80 parts of DMF solution; In DMF, heat to 62°C and keep warm for 40 minutes, add dropwise 2.1 parts of 2,5-dihydroxyterephthalic acid DMF solution (25 parts in total), heat to 70°C, and stir at 80rpm for 2h; S3: add 1 part of amylose, cool to 45°C, and react with rapid stirring at 150rpm for 0.5h. After completion, centrifuge and filter the product, add it to deionized water, and ultrasonically vibrate at 400W for 2.5h until there is no lumpy precipitate in the solution. After completion, the product is centrifuged and filtered and freeze-dried. After completion, it is obtained.

[0110] Comparative Example 8

[0111] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 40 nm.

[0112] Comparative Example 9

[0113] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional polymer is a polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate, and the preparation method comprises the following steps, in parts by mass: 5 parts of trimerized 1,2-propylene glycol are vacuum dehydrated at 120°C for 1.5 hours, then 95 parts of diphenylmethane diisocyanate are added, stirred and heated to 80°C, kept warm for reaction for 2 hours, cooled to 60°C and discharged, and after completion, a polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate is obtained.

[0114] Performance Evaluation

[0115] The following performance tests were performed on the polyurethane foams obtained in the examples and comparative examples. The performance tests with specific values ​​as the results were all averaged from 10 tests and recorded in Tables 1 and 2.

[0116] 1. Viscosity, GB / T2794-2013, test temperature 23±2℃, rotor 29#.

[0117] 2. Anti-sagging, GB / T31113-2014, method 2, rubber plug method.

[0118] 3. Creamy time, surface drying time, HG / T 4574-2014.

[0119] 4. Foam density, GB / T 6343-2009.

[0120] 5. Hardness, ASTM D2240.

[0121] 6. Aspect ratio, measured with calipers.

[0122] 7. U-type waterproof, GMW 17356-2022, no water leakage at room temperature for 1h & 100mm depth, the U-type waterproof test result diagram of Example 1 is as follows Figure 1 shown.

[0123] 8. Pull-out force (dry condition), using test tools (50mm long aluminum clamp) and force sensor, (measuring force range 0~200N, measurement uncertainty: ≤1N), the pulling speed is constant at 20mm / sec, the foam is grasped by the clamp during the test, and a gap of 2mm is retained to ensure that the foam is not damaged. The test takes the average value of 5 tests.

[0124] 9. Pull-out force (wet conditions), using test tools (50mm long aluminum clamp) and force sensors, (force range 0~200N, measurement uncertainty: ≤1N), the pulling speed is constant at 20mm / sec, the foam rubber needs to be completely immersed in deionized water for 2h before testing, the foam rubber is grasped by the fixture during the test, and a gap of 2mm is retained to ensure that the foam rubber shape is not damaged. The test takes the average value of 5 tests.

[0125] 10. Odor, GMW3205; Odor classification: 1: unbearable; 2: very unpleasant odor; 3: unpleasant odor; 4: offensive odor; 5: limit of tolerance; 6: still tolerable; 7: clearly detectable but not offensive; 8: slight odor; 9: just detectable; 10: odorless.

[0126]

[0127]

[0128] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that examples 1 to 3 of the present application have obvious advantages over comparative examples 1 to 9 in terms of mechanical properties, waterproof sealing properties, flame retardant properties and other properties. This is mainly due to the combined effect of the functional particles, functional polymers and other matching raw material solutions specified in the present application. Comparative examples 1 to 9 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A polyurethane foam, characterized in that: It includes component A and component B; The raw materials of component A are calculated by weight: 65-85 parts of polyol composition, 2-5 parts of chain extender, 10-20 parts of flame retardant, 10-15 parts of functional particles, 2-5 parts of thixotropic agent, 0.3-1 parts of catalyst, 1.5-3 parts of foam stabilizer, 1-2 parts of deionized water, 0.4-0.8 parts of antioxidant, and 1.5-2.5 parts of auxiliary agent; The raw materials of component B are calculated by weight: 45-55 parts of polyisocyanate and 45-55 parts of functional polymer; The mass ratio of component A to component B is (95-100): (15-22); The polyol composition is a composition of polyether polyol and polyurea polyol; the mass ratio of the polyether polyol to the polyurea polyol is (40-50): (25-35); The polyurea content of the polyurea polyol is 15-25%; the hydroxyl value of the polyurea polyol is 24-26 mgKOH / g; the viscosity of the polyurea polyol is 1800-2400 mPa·s at 25°C; The chain extender is at least one of ethylene glycol, triethanolamine, diethyltoluenediamine, and polytetramethylene ether glycol bis(p-aminobenzoate); The flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, zinc borate, antimony oxide, expanded graphite, and aluminum oxide; The preparation method of the functional particles comprises the following steps: S1: adding zinc oxide to a DMF solution, adding succinic anhydride and vinyl trimethoxysilane, heating to 70-75°C and keeping warm for 2-4 hours, centrifugally filtering after completion, washing with deionized water and drying to obtain pretreated zinc oxide; S2: mixing the pretreated zinc oxide and zinc nitrate hexahydrate and adding them to DMF, heating to 60-65°C and keeping warm for 30-40 minutes, dropwise adding a DMF solution of 2,5-dihydroxyterephthalic acid, heating to 68-70°C, stirring at 60-80 rpm for 2-2.5 hours; S3: adding amylose, cooling to 45-50°C, rapidly stirring at 120-160 rpm for reaction for 0.5-1 hour, centrifugally filtering the product after completion, adding it to deionized water, and ultrasonically vibrating at 300-400W for 2-3 hours until there is no block precipitation in the solution, and centrifugally filtering the product after completion and freeze-drying, and obtaining the functional particles after completion; The mass ratio of zinc oxide, succinic anhydride and vinyl trimethoxysilane is (3-3.5): (1.5-2): (0.2-0.3); The mass ratio of the pretreated zinc oxide, zinc nitrate hexahydrate, 2,5-dihydroxyterephthalic acid and amylose is (1-1.5): (1.2-2): (2.5-3.5): (1.2-1.6); The auxiliary agent is at least one of polyisobutylene, terminal hydroxyl-modified polybutadiene, hydrogenated rosin methyl ester, and liquid petroleum resin; The average particle size of the zinc oxide is 10-20 nm; The thixotropic agent is a composition of bentonite and modified hydrogenated castor oil; the mass ratio of the bentonite and the modified hydrogenated castor oil is (1.2-1.6): (2.5-3.5); The functional polymer is a polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate; the preparation method of the functional polymer comprises the following steps: vacuum dehydrating trimerized 1,2-propylene glycol at 120-130° C. for 1.5-2 hours, then adding diphenylmethane diisocyanate, stirring and heating to 80-90° C., keeping the temperature for reaction for 2 hours, cooling to 60-65° C., and discharging the material, and after completion, a polymer of trimerized 1,2-propylene glycol and diphenylmethane diisocyanate is obtained; The mass ratio of trimerized 1,2-propylene glycol to diphenylmethane diisocyanate is (1-1.5): (4-4.5); The NCO content index of the functional polymer is 20-24%; the viscosity of the functional polymer is 1000-1500 mPa·s at 25°C; The mass ratio of the polyol composition, the functional particles and the auxiliary agent is (70-80): (12-15): (1.8-2.2); The polyether polyol is propylene oxide-ethylene oxide copolyether triol; the primary hydroxyl content of the propylene oxide-ethylene oxide copolyether triol is 70-90%; the weight average molecular weight of the propylene oxide-ethylene oxide copolyether triol is 4500-5500Da; The hydroxyl value of the propylene oxide-ethylene oxide copolyether triol is 34-38 mgKOH / g; the viscosity of the propylene oxide-ethylene oxide copolyether triol is 800-1000 mPa·s at 25°C.

2. The polyurethane foam according to claim 1, characterized in that: The flame retardant is a composition of aluminum hydroxide and zinc borate; the mass ratio of the aluminum hydroxide to the zinc borate is (4-6): (1-1.5).

3. The polyurethane foam according to claim 2, characterized in that: The average particle size of the flame retardant is 1-3 μm.

4. The polyurethane foam according to claim 3, characterized in that: The foam stabilizer is a hydrosilylation polymer of improved polyether and polysiloxane; and the auxiliary agent is terminal hydroxyl-modified polybutadiene.

5. A method for preparing the polyurethane foam according to any one of claims 1 to 4, characterized in that: The specific steps include: S1: Add the polyol composition, chain extender, flame retardant, functional particles and thixotropic agent into a reactor and mix and stir until there are no obvious undispersed particles, then heat to 70~90℃, stir at 200~300rpm for reaction for 50~70min, then cool to 30~35℃ at 1~1.5℃ / min to obtain a premixed base; S2: Add deionized water to the premixed base to control the moisture content at 1.2~2wt%, then add a foam stabilizer and a catalyst, stir and disperse for 30~50min, then blow at 100~150rpm for mixing for 20~30min to obtain component A; S3: Add polyisocyanate and functional polymer into a vacuum reactor, heat to 60~65℃, stir at 40~60rpm for 30~40min, and use nitrogen to break the air to produce glue to obtain component B; S4: When using, mix component A and component B according to the proportion and glue them, and the result is obtained after completion.